How diverse is hotel website accessibility? A study in the central region of Portugal using web diagnostic tools - Teixeira, Pedro (2022)
Accessible tourism is a very important growth market that should not be ignored by the tourism industry, not only due to legal obligations and social responsibility but also because of business opportunities. However, people with special needs face various constraints in accessing tourism products. The absence of accessible information is one of the main barriers that people with special needs face when they intend to travel. The Internet represents one of the most important information sources in tourism. However, a limited number of studies examine the use of the Internet in the accessible tourism market, specifically website accessibility. To extend knowledge in this field, this study aims to analyse the website accessibility of hotels and Pousadas de Portugal located in the Central Region of Portugal. A sample of 306 websites was analysed based on Web Content Accessibility Guidelines (WCAG) 2.0, using automatic web diagnostic tools (AccessMonitor and TAW). This analysis was performed considering the A, AA and AAA conformance levels of WCAG. Findings reveal that the web accessibility level of the hotels analysed is low, with the ‘Perceivable’ and ‘Robust’ guidelines being the most critical. Moreover, there are differences in the web accessibility levels in terms of hotel category. Contrary to what was expected, the higher category hotels present the lowest level of web accessibility. These results can help hotel managers and web designers to improve communication with an important growth market – accessible tourism.